Knowledge levels of medical faculty students and residents about ionizing radiation - İkiışık, Hatice; Sever, F; Çakir, M; Yazar, RÖ; Taşkin, S; Gülle, MS; Bayram, F; Uzun, NM; Kurşun, MA; Fanİ, FB; Laçalar, GT; Gürel, S; et al. (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
This study aimed to evaluate the knowledge levels of medical school students and residents about ionising radiation. The study is designed as descriptive research, and it was conducted with 369 medical school students and residents. A survey form was used in the research. A Chi-square test was used to compare categorical variables. In the study, 369 people were reached within the scope of the research. A total of 60.7% of the research participants were clinical medicine students (4th, 5th, 6th grade) and 39.3% were residents. A total of 42.0% of the participants of the study were male, 58.0% were women. It was found that 17.9% of the clinical medical students and 18.6% of the residents had sufficient knowledge of ionising radiation (p=0.002). A total of 87.0% of the participants in the study answered correctly that magnetic resonance imaging (MRI) does not contain radiation and 93.5% answered correctly that ultrasonography (USG) does not contain radiation. 74.8% of the participants stated that having knowledge about ionising radiation would contribute to “protecting sensitive groups from ionising radiation” in medical practice. This ratio is 77.2% in clinical medicine students and 71.0% in residents. The study found that knowledge levels of medical faculty students and residents about ionising radiation were insufficient. Medical students and residents are recommended to be trained on radiation and the radiological requests of residents to be evaluated.